Calidad de vida y envejecimiento saludable en adultos mayores del barrio Colinas Lojanas de la ciudad de Loja - Salinas Moncayo, Cinthya Elizabeth (2024)
The older adult has an interaction between different characteristics of human existence such as housing, clothing, food, education and human freedoms; each of these contribute in different ways to allow a good state of well-being, bearing in mind the evolutionary process of aging, therefore the quality of life is related to personality, well-being and satisfaction with the life he/she leads, evidence related to his/her own experience, health, degree of social and environmental interaction, with multiple factors. The purpose of this study was to evaluate the quality of life, identify healthy aging according to sex and age group, and establish the relationship between quality of life and healthy aging in older adults of the Colinas Lojanas neighborhood, through a quantitative approach, crosssectional cohort, with a sample of 50 participants in which quality of life and healthy aging were measured through the application of the World Health Organization's questionnaire for quality of life in adults (WHOQOL-BREF) and the active aging scale. Obtaining a predominance of the female sex, the elderly group in both men and women showed an average quality of life of 60% (n=6) and 50% (n=20) respectively. On the other hand, in men and women, regular healthy aging represented 60% (n=6) and 50% (n=20) in the elderly group. When establishing the statistical relationship, it was found that 94% of the population reported average quality of life and regular healthy aging. The reliability of the instruments was determined with the Cronbach's alpha statistical test with an internal reliability of 0.77 and 0.83, respectively